Graph Querying Meets HCI: State of the Art and Future Directions - Choi, Byron (2017)
Querying graph databases has emerged as an important research problem for real-world applications that center on large graph data. Given the syntactic complexity of graph query languages (e.g., SPARQL, Cypher), visual graph query interfaces make it easy for non-expert users to query such graph data repositories. In this tutorial, we survey recent developments in the emerging area of visual graph querying paradigm that bridges traditional graph querying with human computer interaction (HCI). We discuss manual and data-driven visual graph query interfaces, various strategies and guidance for constructing graph queries visually, interleaving processing of graph queries and visual actions, and visual exploration of graph query results. In addition, the tutorial suggests open problems and new research directions. In summary, in this tutorial we review and summarize the research thus far into HCI and graph querying in the database community, giving researchers a snapshot of the current state of the art in this topic, and future research directions.